Pengembangan Sistem Informasi Penyewaan Billboard di PT Tecma Mitratama Advertindo - Endang Ayu Susilawati; Eva Novianti; Sultan Satrio Ichsan (Prodi Teknologi Informasi Universitas Darma Persada, 2025)
The billboard rental process at PT Tecma Mitratama Advertindo currently encounters issues, particularly in calculating rental prices for periods outside the predefined options of one, three, six, and twelve months. When customers request rental durations beyond these standard periods, prices must be calculated manually using a calculator, resulting in delays in issuing rental offer letters. This study aims to develop a billboard rental information system integrated with the marketing division's workflow. The system is expected to streamline the rental process and enable real-time monitoring of billboard rental status. The system development process includes requirements analysis, system design, and web-based interface implementation. The results indicate that the developed system can reduce reliance on manual processes and enhance the efficiency of the marketing division’s operations.